2008
DOI: 10.4088/jcp.v69n0417
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Depression in Women Hospitalized for Obstetric Risk

Abstract: Objective-Little is known about depression during pregnancy in women with high maternal or fetal risk, as this population is often excluded from research samples. The aim of this study was to evaluate depressive symptoms and known risk factors for depression in a group of women hospitalized with severe obstetric risk. Results-Fifty-seven of the 129 women (44.2%) scored 11 or greater on the EPDS, and at least 25/129 (19%) met the DSM-IV criteria for Major Depressive Disorder (MDD). Mothers reporting high attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
1
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 32 publications
6
83
1
12
Order By: Relevance
“…Two of the 7 studies were prospective cohort studies [13,15], and six were cross-sectional studies [10,14,16,17,18]. Both of the prospective studies had assessment points both antenatally and postnatally [13,15].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of the 7 studies were prospective cohort studies [13,15], and six were cross-sectional studies [10,14,16,17,18]. Both of the prospective studies had assessment points both antenatally and postnatally [13,15].…”
Section: Methodsmentioning
confidence: 99%
“…The size of the samples ranged from 20 women to 367 couples, and the size of the control samples ranged from 55 to 200. The vast majority of studies included < 100 women [13,15,16,17], while three studies included more than 100 high-risk pregnant women [10,14,18]. Only one study in this review [15] provided a power calculation.…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nesse sentido, Brandon et al (2008) Gestantes são pós-natal, podendo causar baixo peso ao nascer e prematuridade, afetando o desenvolvimento da criança. Para Perosa et al (2008) "os efeitos da depressão materna não se limitam ao atraso no desenvolvimento dos primeiros tempos de vida, mas podem ocasionar alterações na interação mãe-filho na primeira infância, e causar prejuízos no desenvolvimento cognitivo e comportamental, em longo prazo" (p.31).…”
Section: Discussionunclassified
“…In a study of women hospitalised for severe obstetric risk, findings indicated a higher prevalence rate of major depressive disorder in women with severe obstetric risk (19.4 per cent) than that repor ted in low-risk pregnancy groups. 9 Depression is a stress disorder that is related to social disadvantage and poverty. Reported rates of depression in pregnancy are higher in developing than developed countries: one study of over 600 pregnant women in rural Pakistan found a point prevalence of 25 per cent with depression.…”
Section: Progress In Neurology and Psychiatrymentioning
confidence: 99%